The Role of Instagram Social Media in Marketing Mahamerujaya Travel Products, Malang City - Selviasari, Rike; Mukhlis, Imam (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to determine how developments in information technology have changed the landscape of the marketing world in recent years. Marketing, which was originally traditional and conventional, has now really developed into the digital realm. One example of the use of social media Instagram as a digital marketing medium used by Mahameru Jaya Tour and Travel in marketing its general and religious tourism products. One way to optimize the use of Instagram social media in digital marketing of tourism products on this trip is how to manage the marketing system using Instagram social media, and also knowing the obstacles to using Instagram social media as a digital marketing medium. The method used in this research is a qualitative method which produces descriptive data in the form of oral and written expressions from the subjects studied. In this case, the researcher conducted interviews with the parties concerned, especially in the field of marketing Mahameru Jaya Tour and Travel products in the city of Malang. The results show that the existence of Instagram as a social media provides innovation related to marketing digitalization and corporate form to increase consumer interest in using this travel service